A Bottleneck Hypothesis Test: L1 American English Learners’ Comprehension of Morphology and Syntax in L2 Urdu - Karishma Khatoon; Sabahuddin Ahmad (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
The paper investigates L1 English learners' knowledge of syntax and morphology in L2 Urdu to test the bottleneck hypothesis. The Bottleneck Hypothesis examines what is difficult and easy to learn in L2. According to the hypothesis, acquiring a second language functional morphology is more challenging than syntax. The present study tested whether subject verb agreement is more complicated than word ordering in the second language L2 (Urdu). The study differs in several respects (Methodology and Languages L1& L2) from other previous studies (Salbakova, 2008, 2013, 2014, 2018; Basnet, 2013; Jensen et al., 2020; Rajabi, 2022). Content Analysis and Quantitative methods have been used in this study to get the answer to the research questions and prove the research hypothesis. The result indicates that the learners struggle more in acquiring subject verb agreement than word order. The study concludes that the findings impart conditional support to the Bottleneck Hypothesis.